2016
DOI: 10.1088/1757-899x/136/1/012054
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of low ring polycylic aromatic biodegradation

Abstract: Abstract. Polycyclic aromatic hydrocarbons (PAHs) are recalcitrance and persistence that finally turn into problematic environmental contaminants. Microbial degradation is considered to be the primary mechanism of PAHs removal from the environment due to its organic criteria. This study is carried out to optimize degradation process of low ring PAHs. Bacteria used in this study was isolated from sludge collected from Kolej Mawar, Universiti Teknologi MARA, Shah Alam, Selangor. Working condition namely, substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Working conditions, namely, substrate concentration, bacteria concentration, pH, and temperature, have to be optimized. Results from the optimization study of biodegradation indicated that the maximum rate of PAH removal occurred at 100 mg L −1 of PAHs, 10% bacteria concentration, pH 7.0, and 30 °C (Othman et al 2016 ). For the degradation of pesticides, bacteria must possess enzymes that cleave the ring of the aromatic halogen compound (PCP) (Arora et al 2010 ; Arora and Bae 2014 ; Zhou et al 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Working conditions, namely, substrate concentration, bacteria concentration, pH, and temperature, have to be optimized. Results from the optimization study of biodegradation indicated that the maximum rate of PAH removal occurred at 100 mg L −1 of PAHs, 10% bacteria concentration, pH 7.0, and 30 °C (Othman et al 2016 ). For the degradation of pesticides, bacteria must possess enzymes that cleave the ring of the aromatic halogen compound (PCP) (Arora et al 2010 ; Arora and Bae 2014 ; Zhou et al 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Umumnya, bakteri perairan tumbuh baik pada kondisi perairan dengan pH 6,5-7,5 (Respati, 2017) dan suhu 20 hingga 40°C (Supriyati & Rahayu, 2011). Nilai pH menjadi faktor yang memengaruhi proses degradasi logam berat dan poliaromatik hidrokarbon oleh mikroba dan umumnya mampu mendegradasi dengan baik pada kisaran 7,0-7,5 (Othman et al, 2016). Kadar oksigen terlarut (DO) digunakan mikroorganisme perairan untuk metabolisme guna menghasilkan energi (Jurtshuk, 1996) dan merombak polutan organik (Bara'padang et al, 2019).…”
Section: Parameter Fisikokimia Perairanunclassified